2011
DOI: 10.1007/s10142-011-0210-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial proteomics analysis of tumorigenic and metastatic breast cancer markers

Abstract: Mitochondria are key organelles in mammary cells responsible for several cellular functions including growth, division, and energy metabolism. In this study, mitochondrial proteins were enriched for proteomics analysis with the state-of-the-art two-dimensional differential gel electrophoresis and matrix-assistant laser desorption ionization-time-of-flight mass spectrometry strategy to compare and identify the mitochondrial protein profiling changes between three breast cell lines with different tumorigenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 34 publications
1
22
1
1
Order By: Relevance
“…High levels of SCaMC-1 were previously found by screening approaches in colorectal carcinomas, 29 breast cancer 30 and in several cancer cell lines. 15,31 Our in silico studies confirmed and extended these findings to 67 different tumour types where SCaMC-1 expression significantly exceeded its expression in their normal tissue counterpart.…”
Section: Discussionmentioning
confidence: 80%
“…High levels of SCaMC-1 were previously found by screening approaches in colorectal carcinomas, 29 breast cancer 30 and in several cancer cell lines. 15,31 Our in silico studies confirmed and extended these findings to 67 different tumour types where SCaMC-1 expression significantly exceeded its expression in their normal tissue counterpart.…”
Section: Discussionmentioning
confidence: 80%
“…SCaMC is one of the two carriers responsible for transporting ATP. While AAC accounts for the bulk ADP/ATP recycling in the matrix by exporting newly synthesized ATP out of the matrix while importing ADP for continuous synthesis (Traba et al, 2009b), the transport activity of SCaMC is important for mitochondrial activities that depend on adenine nucleotides, such as gluconeogenesis, mitochondrial biogenesis and mitochondrial DNA maintenance (Amigo et al, 2013; Cavero et al, 2005; Chen et al, 2011; Kucejova et al, 2008; Llorente-Folch et al, 2013; Satrustegui et al, 2007). SCaMC is abundant, and to date, five major paralogs have been identified, SCaMC-1/SLC25A24, SCaMC-2/SLC25A25, SCaMC-3/SLC25A23 (Bassi et al, 2005; del Arco and Satrustegui, 2004; Fiermonte et al, 2004; Mashima et al, 2003), SCaMC-1L (Amigo et al, 2012) and SCaMC-3L (Traba et al, 2009a), most of which have several alternative spliced variants (del Arco and Satrustegui, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these protein visualization methods often have narrow linear dynamic ranges of detection, making them unsuitable for the analysis of biological samples where protein copy numbers vary enormously. A significant improvement in the ability to use gel-based methods for protein quantitation and detection was achieved with the introduction of 2D-difference gel electrophoresis (2D-DIGE), which enables co-detection of several samples on the same 2-DE gel, so avoiding gel-to-gel variation [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%